Fiber to The Home (FTTH) Network Design Using Gigabit Passive Optical Network (GPON) Technology Using Link Power Budget and Rise Time Budget Analysis in Cibeber Village Tasikmalaya - Nurul Ikhwan; Hani Rubiani; Noerlaelly Barorroh Taufik Abdul Ghofur; Yang Zhu (International Journal of Quantitative Research and Modeling, 2023)
Fiber optic is a transmission medium that can transmit information with large capacity. One of the developments in local fiber access networks is FTTH (Fiber to The Home). The construction of the FTTH network uses Gigabit Passive Optical Network (GPON) technology so that it can provide broadband services to customers with a wider range. This research was studied by designing FTTH based on GPON technology in Cibeber Village, Manonjaya District. The existing condition of the FTTH network in Cibeber Village is that there are 2 Optical Distribution Points (ODP) for 20 customers with each ODP having 10 subscribers. From the results of the location survey by measuring the distance to each customer, the furthest distance to the customer for the two ODPs was obtained, so that 2 new ODPs were needed for the design. From the design of the new optical network infrastructure, it has been analyzed using the link power budget and rise time budget method based on the customer with the farthest distance before the addition of ODP has a Power Receive sensitivity of -16.631 dBm to -15.631 dBm on the uplink and -16.644 dBm to -15.574 dBm on the downlink, these results are in accordance with the expected standard, which ranges from -8 dBm to -27 dBm. In calculating the value of the rise time budget for customers after the addition of ODP, it has a value of 0.2044 ns to 0.2039 ns on the uplink and 0.2188 ns to 0.21574 ns on the downlink. This value is still below the standard time limit set by PT. Telkom Indonesia 0.56 ns for uplink and 0.292 ns for downlink. So based on this the results of the design are feasible to implement.